EVALUATION OF THE E-RETRIBUTION PROGRAM FOR MARKET SERVICES IN SIDOARJO REGENCY (CASE STUDY: LARANGAN MARKET) - Sari, Risa Yunia Imanda; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the implementation of the e-retribution program in market services in Sidoarjo Regency, focusing specifically on Larangan Market. The objective is to assess the effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy of the digital-based retribution system in improving service delivery to traders. Method: A qualitative descriptive research method was employed. Data collection techniques included interviews, observations, field notes, and the use of both primary and secondary sources. The study used purposive sampling, selecting key informants such as Mr. Herlambang (Head of the UPTD for Regional Markets) and Mr. Joko (Trade Analyst Expert at the Sidoarjo Regency Department of Industry and Trade). Data analysis was conducted using the Miles and Huberman model: data collection, data reduction, data presentation, and conclusion drawing. Results: Findings show that the e-retribution application significantly facilitates market service processes. The system is effective in operation, efficient in saving time, adequate in meeting trader needs, equitable in reaching all traders, responsive to user feedback, and accurate due to digital record-keeping. Novelty: This study contributes to the growing body of literature on digital governance in local public services by providing empirical evidence on the successful implementation of e-retribution systems at the market level. It highlights the practical benefits of digital transformation for public service efficiency, especially in traditional market settings.